2004
DOI: 10.1111/j.1467-9507.2004.000265.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's Anger, Emotional Expressiveness, and Empathy: Relations with Parents’ Empathy, Emotional Expressiveness, and Parenting Practices

Abstract: In Roberts and Strayer (1996)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
2
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 75 publications
6
113
2
10
Order By: Relevance
“…Exceptions are the studies by Strayer and Roberts (2004) and Warren and Stifter (2008). Strayer and Roberts (2004) did not directly observe parents' behavior but found that children who reported greater parental rejection and physical discipline were less accurate when reporting their emotion facial display. Also parents' own reports of lower levels of warmth were related to lower levels of facial-verbal convergence in their children.…”
Section: Defining and Measuring Children's Emotional Awarenessmentioning
confidence: 97%
See 1 more Smart Citation
“…Exceptions are the studies by Strayer and Roberts (2004) and Warren and Stifter (2008). Strayer and Roberts (2004) did not directly observe parents' behavior but found that children who reported greater parental rejection and physical discipline were less accurate when reporting their emotion facial display. Also parents' own reports of lower levels of warmth were related to lower levels of facial-verbal convergence in their children.…”
Section: Defining and Measuring Children's Emotional Awarenessmentioning
confidence: 97%
“…With regard to measuring these constructs, we developed a new observational measure of emotional validation/invalidation based on the key conceptual features of nonjudgmental accurate reference to the emotion or emotional perspective of the other (emotional validation) versus judgmental, dismissive, or inaccurate reference to the emotion or emotional perspective of the other (emotional invalidation). 1 We measured accuracy of emotional awareness by using the convergence between the children's expression of emotion and their subsequent verbal report of it (Casey, 1993: Strayer & Roberts, 2004.…”
Section: The Role Of Parental Emotional Validationmentioning
confidence: 99%
“…De manera general, la empatía es una reacción que incluye la aprehensión o comprensión de estados y/o condiciones emocionales de otros; es una respuesta o conjunto de respuestas emocionales y cognitivas que concuerdan con las experiencias emocionales de otras personas (Strayer & Roberts, 2004). En todas las definiciones de empatía se indica que tanto los aspectos afectivos como los cognitivos son necesarios para que ésta ocurra.…”
Section: Ntroducciónunclassified
“…Although direct linkages between parent and child empathy do not always emerge in research (Strayer & Roberts, 1989), parent empathy may be associated with particular parenting practices such as low coercive control and encouragement of emotional expressiveness, even for negative emotions. These practices, in turn, relate to higher empathy in children (Strayer & Roberts, 2004). Socialization that includes parental warmth, but also the demonstration of -xprosocial behavior and explicit references to the reasoning for prosocial actions, appears to be most successful in eliciting prosocial behavior in children (Yarrow, Scott, & Waxler, 1973).…”
Section: Concern For Othersmentioning
confidence: 99%